Preclinical imaging methods for assessing the safety and efficacy of regenerative medicine therapies. (December 2017) - Scarfe, Lauren; Brillant, Nathalie; Kumar, J.; Ali, Noura; Alrumayh, Ahmed; Amali, Mohammed; Barbellion, Stephane; Jones, Vendula; Niemeijer, Marije; Potdevin, Sophie; Roussignol, Gautier; Vaganov, Anatoly; et al.
Abstract Regenerative medicine therapies hold enormous potential for a variety of currently incurable conditions with high unmet clinical need. Most progress in this field to date has been achieved with cell-based regenerative medicine therapies, with over a thousand clinical trials performed up to 2015. However, lack of adequate safety and efficacy data is currently limiting wider uptake of these therapies. To facilitate clinical translation, non-invasive in vivo imaging technologies that enable careful evaluation and characterisation of the administered cells and their effects on host tissues are critically required to evaluate their safety and efficacy in relevant preclinical models. This article reviews the most common imaging technologies available and how they can be applied to regenerative medicine research. We cover details of how each technology works, which cell labels are most appropriate for different applications, and the value of multi-modal imaging approaches to gain a comprehensive understanding of the responses to cell therapy in vivo.